The Impact an Oratory Project generates to Primary School Students who live in Rural Areas of Cartago - Amador-Solano, María Gabriela (2014)
This article aims at showing the development and relevance of an extension project in seven rural schools located in “circuito 05” in the central area of Cartago. The main goal is to enhance oral communication in elementary school students. The project was designed as a training workshop for the teachers in the chosen schools in order to be taught to students by implementing an oratory club. In each student´s dissertation, the researchers observed the enthusiasm that the project caused in the schools. Objectives, contents, activities, assessment and observations were designed in a didactic plan to be used upon needs of institutions.